Prodi pendidikan bahasa arab UIN Malang meraih akreditasi unggul: Sebuah pencapaian strategis menuju internasionalisasi mutu pendidikan - Syarifatunnazah, Ety (Maliki Interdisciplinary Journal, 2025)
Improving the quality of higher education delivery is an inevitable need in the current era of technological disruption and global progress. In facing the waves of change marked by the Industrial Revolution 4.0 and the emergence of the concept of society 5.0, universities must transform from administrative institutions to innovation centers oriented towards quality sustainability. The Arabic Language Education Program at UIN Maulana Malik Ibrahim Malang received “Excellent” accreditation from LAMDIK with a score of 390, as stated in Decree No. 1490/SK/LAMDIK/Ak/S/X/2024, valid from October 7, 2024, to October 6, 2029. This article discusses quality improvement strategies, including curriculum development based on OBE, lecturer qualification enhancement, digital learning innovation, and academic collaboration. This achievement reflects institutional quality and impacts graduate competitiveness and program reputation. The findings show that the “Excellent” accreditation resulted from a collective and continuous quality-oriented effort.